2021
DOI: 10.1038/s41598-021-90149-y
|View full text |Cite
|
Sign up to set email alerts
|

Next generation proteomics with drug sensitivity screening identifies sub-clones informing therapeutic and drug development strategies for multiple myeloma patients

Abstract: With the introduction of novel therapeutic agents, survival in Multiple Myeloma (MM) has increased in recent years. However, drug-resistant clones inevitably arise and lead to disease progression and death. The current International Myeloma Working Group response criteria are broad and make it difficult to clearly designate resistant and responsive patients thereby hampering proteo-genomic analysis for informative biomarkers for sensitivity. In this proof-of-concept study we addressed these challenges by combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Proteome analysis was performed for 35 MM patient samples as described previously (Tierney et al, 2021). Briefly, CD138 + cells were lysed in RIPA buffer (Cell Signaling Technology, Danvers, MA, United States).…”
Section: Proteome Analysismentioning
confidence: 99%
“…Proteome analysis was performed for 35 MM patient samples as described previously (Tierney et al, 2021). Briefly, CD138 + cells were lysed in RIPA buffer (Cell Signaling Technology, Danvers, MA, United States).…”
Section: Proteome Analysismentioning
confidence: 99%
“…Complementary to molecularly guided precision medicine, drug testing directly on patient biopsies is increasingly successfully implemented for personalized treatment selection [40][41][42] and analysis of drug sensitivity [43][44][45] . For MM, several ex vivo drug screening studies have been performed with bulk viability assays informing on possible treatment options, including BCL2 inhibition by venetoclax [46][47][48] . We have recently reported that image-based ex vivo drug testing (called pharmacoscopy; PCY) recommends treatments that lead to significant progression-free survival improvement for patients suffering from relapsed/refractory hematological malignancies, compared to the patient's own responses to previous treatment 40,41,49 .…”
Section: High-throughput Phenotypic Detection Of Myeloma Cellsmentioning
confidence: 99%
“…However, NGP can narrow down multiple non-specific drugs to targetspecific or patient-specific drugs. For example, with the help of NGP and drug sensitivity score (DSS) determination, Tierney et al constructed a theranostic profile for multiple myeloma patients to predict the least/most sensitive drug among 5 drug molecule panels [133].…”
Section: Proteomics-based Precision and Personalized Therapeutic Regi...mentioning
confidence: 99%
“…For example, with the help of NGP and drug sensitivity score (DSS) determination, Tierney et al. constructed a theranostic profile for multiple myeloma patients to predict the least/most sensitive drug among 5 drug molecule panels [133]. Additionally, in a multidisciplinary proteomic study, through phosphoproteomics, interactomics, and immunopeptidomics, CT45 (a protein involved in the DNA damage pathway) was reported as an enhancer of chemotherapy and immunotherapy in ovarian cancer [134].…”
Section: Proteomics‐based Precision and Personalized Therapeutic Regi...mentioning
confidence: 99%